Subtype-specific regulatory network rewiring in acute myeloid leukemia - Assi, Salam A.; Imperato, Maria Rosaria; Coleman, Daniel J. L.; Pickin, Anna; Potluri, Sandeep; Ptasinska, Anetta; Chin, Paulynn Suyin; Blair, Helen; Cauchy, Pierre; James, Sally R.; Zacarias-Cabeza, Joaquin; Gilding, L. Niall; et al. (Nature genetics, 2019)
Acute myeloid leukemia (AML) is a heterogeneous disease caused by a variety of alterations in transcription factors, epigenetic regulators and signaling molecules. To determine how different mutant regulators establish AML subtype–specific transcriptional networks, we performed a comprehensive global analysis of cis-regulatory element activity and interaction, transcription factor occupancy and gene expression patterns in purified leukemic blast cells. Here, we focused on specific subgroups of subjects carrying mutations in genes encoding transcription factors (RUNX1, CEBPα), signaling molecules (FTL3-ITD, RAS) and the nuclear protein NPM1). Integrated analysis of these data demonstrates that each mutant regulator establishes a specific transcriptional and signaling network unrelated to that seen in normal cells, sustaining the expression of unique sets of genes required for AML growth and maintenance. Integrated analysis of transcriptome, open chromatin region and chromatin conformation capture data from subjects with acute myeloid leukemia (AML) harboring defined transcription factor and signaling molecule alterations provide insights into the subtype-specific regulatory network in AML.